Fattening and slaughtering examination of Hungarian Racka sheep in extensive and intensive conditions - Nagy, László; Gáspárdy, András; Toldi, Gyula; Bodó, Imre; Komlósi, István (Acta Agraria Kaposváriensis, 2007)
Performance of the Hortobágyi Racka in both colour types was evaluated in the course of a comparative breed test in extensive and intensive fattening. The other sheep genotypes were the Hungarian Merino, German Mutton Merino, Cigaja Milk sheep, Cigaja and British Milk sheep, respectively. Significant differences of the breeds’ fattening, dissection and deboning performances were determined by variance analysis. During fattening the Racka showed the lowest average daily gain and the highest fat deposition in intensive conditions. Muscle to bone ratio of the Racka breed was higher than that of the other breeds in intensive conditions and based on the dissection and deboning the Rackas’ performance was higher for bone to muscle ratio than that of the Cigaja Milk sheep in extensive conditions.